THE MAIN CHARACTERISTICS OF THE MANAGEMENT OF SEASONAL STABILITY OF TOURIST FLOWS IN UZBEKISTAN (Marketing Journal, 2025)
This article analyzes the theoretical aspects of the problem of seasonality observed in the fiyeld of tourism in Uzbekistan. As a result of the uneven distribution of the tourist flow throughout the year, it is noted that such negative consequyences as a decrease in yeconomic yefficiyency, incomplete use of infrastructure, temporary yemployment and stagnation in the service sector occur. Based on the research of international and domestic sciyentists, theoretical models of seasonality management have been s tudiyed and practical proposals and recommendations have been developed to mitigate seasonality in the conditions of Uzbekistan. The mechanisms of 105 stabilization of seasonal tourism are based, such as diversification, territorial specialization and the development of domestic tourism.
Keywords: tourism; seasonality; tourist flow; yeconomic yefficiyency; infrastructure; diversification; Sustainable Development; domestic tourism; service; analysis